Management Practices, Faculty Self-Efficacy, and Institutional Performance: A Narrative Review - Felix, Eugelyn R.; Guzman, Rodel B. (Innovare Journal of Education, 2025)
The relationship between management practices, faculty self-efficacy, and institutional performance is a critical area of study in higher education research. Effective management practices provide strategic leadership, governance, and resource allocation that influence faculty experiences and institutional efficiency. Faculty self-efficacy, defined as educators’ belief in their ability to teach, conduct research, and engage in institutional activities, serves as a mediating factor that determines how well management strategies translate into academic success. Institutional performance, measured through indicators such as effectiveness, efficiency, equity, transparency, accountability, and sustainability, reflects the overall success of an institution in fulfilling its mission and adapting to evolving educational landscapes. These three constructs interact in a dynamic and reciprocal manner, where management practices shape faculty confidence, faculty engagement drives institutional outcomes, and institutional performance influences future management strategies and faculty experiences. This literature review explores the interrelationship among these constructs, drawing from empirical studies and theoretical frameworks to analyze how leadership approaches, faculty development programs, and governance structures affect faculty self-efficacy and institutional success. The findings suggest that institutions with strong management practices and high faculty self-efficacy tend to perform better in student learning outcomes, research productivity, and stakeholder satisfaction. However, research gaps remain in understanding the long-term impact of faculty self-efficacy on institutional performance, cross-cultural variations in management strategies, and the role of digital transformation in shaping these relationships. Addressing these gaps will provide valuable insights for higher education leaders seeking to enhance institutional effectiveness through evidence-based policies and faculty support initiatives.